-3-(8x-4)=3(x+2)+7

Simple and best practice solution for -3-(8x-4)=3(x+2)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3-(8x-4)=3(x+2)+7 equation:


Simplifying
-3 + -1(8x + -4) = 3(x + 2) + 7

Reorder the terms:
-3 + -1(-4 + 8x) = 3(x + 2) + 7
-3 + (-4 * -1 + 8x * -1) = 3(x + 2) + 7
-3 + (4 + -8x) = 3(x + 2) + 7

Combine like terms: -3 + 4 = 1
1 + -8x = 3(x + 2) + 7

Reorder the terms:
1 + -8x = 3(2 + x) + 7
1 + -8x = (2 * 3 + x * 3) + 7
1 + -8x = (6 + 3x) + 7

Reorder the terms:
1 + -8x = 6 + 7 + 3x

Combine like terms: 6 + 7 = 13
1 + -8x = 13 + 3x

Solving
1 + -8x = 13 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
1 + -8x + -3x = 13 + 3x + -3x

Combine like terms: -8x + -3x = -11x
1 + -11x = 13 + 3x + -3x

Combine like terms: 3x + -3x = 0
1 + -11x = 13 + 0
1 + -11x = 13

Add '-1' to each side of the equation.
1 + -1 + -11x = 13 + -1

Combine like terms: 1 + -1 = 0
0 + -11x = 13 + -1
-11x = 13 + -1

Combine like terms: 13 + -1 = 12
-11x = 12

Divide each side by '-11'.
x = -1.090909091

Simplifying
x = -1.090909091

See similar equations:

| -14x+7=21 | | -x-2(x+1)=1-7x | | 3(2x+8)=2(2x+40) | | 10x-7y=44 | | 5+2(x+3)=-x-6 | | 0=t^2+t-6 | | a+5=-16 | | -3(5+7p)=33-5p | | -2(x+7)=4x-7 | | -4=13.7 | | 15-3x=12-5x | | 4w(w-6)-2w^2=2w^2+8w-4 | | 2+3n=0.8n+18 | | 14-x=3x-2 | | x^3+5x^2+16x+80=0 | | 4/28=x/147 | | -7(x-6)-8=-5x+40 | | 5W+W=36 | | h=9(8m-9r) | | 6(-6-5)-6=0 | | ln(x+11)+ln(x-3)=2lnx | | 0=a^2-18a+72 | | 4x+6=-7x-7 | | -15t^2+60t=0 | | 5t+6-8t=30 | | 24t^2+19t+2=0 | | .25p+7=3 | | (2x^2-5x-3)=0 | | 2q+30=6-4q | | 50x=20x+10 | | 3x+5+6x=113 | | 50x=20x+30 |

Equations solver categories